(untitled) (Journal of Ideas in Health, 2023)
Background: Leprosy has over time been seen as a symbol of shame and stigmatization as people affected by leprosy continue to be stigmatized and discriminated against even after they have been cured. The study aimed to assess the perceived levels of stigmatization, psychosocial well-being, and self-esteem among individuals living at a leprosy center in South-West, Nigeria. Methods: A descriptive cross-sectional design of face-to-face research was conducted in a leprosy center using a simple random technique. The study instrument was a self-structured questionnaire containing sociodemographic details, questions on stigmatization towards the individual affected by leprosy and their family members, and questions regarding their psychosocial well-being adapted from literature, as well as questions adapted from the validated Rosenberg Self Esteem Scale (RSES) by Morris Rosenberg to assess their self-esteem. Data were analyzed with the aid of SPSS version 26 software. Results: A total of 134 participants were included in the study. Most of the participants were females (61.2%) within the age range of 21- 40 years old (32.8%), and are students (25.4%). Out of the 134 participants, 29.1% (39) of them were affected by leprosy. The participants perceived a high level of stigmatization (37.3%), a high level of psychosocial well-being (38.8%), and demonstrated a moderate level of self-esteem (50.7%). The male gender perceived both low (B = -3.054, p = 0.004) and high (B = -1.84, p = 0.049) stigmatization at p< 0.05. The married (B = -5.421, p = 0.004), the Christians (B = 5.424, p = 0.043) and Islamic (B = 7.743, p = 0.011) participants perceived low stigmatization at p< 0.05. The participants within the age range 21 - 40 (B = 6.25, p = 0.019) and 61 – 80 years (B = 7.29, p = 0.017) perceived high psychosocial well-being while the single (B = -4.43, p = 0.049) and married (B = -5.26, p = 0.017) participants perceived low psychosocial well-being at p< 0.05. None of the demographic factors had relationships with self-esteem at p< 0.05. The perceived levels of stigmatization (r= 0.314, p= 0.0001) and psychosocial well-being (r= 0.225, p= 0.009) are associated with the level of self-esteem at p< 0.05. Conclusion: This study concludes that the individuals affected by leprosy and their family members living at the leprosy center experienced a high level of stigmatization and, a high level of psychosocial well-being but had moderate self-esteem.